SENP3-Mediated PPARγ2 DeSUMOylation in BM-MSCs Potentiates Glucocorticoid-Induced Osteoporosis by Promoting Adipogenesis and Weakening Osteogenesis - Zhang, Yongxing; Chen, Yang; Sun, Hangxiang; Zhang, Wenkan; Zhang, Lingling; Li, Hengyuan; Huang, Xin; Yang, Jie; Ye, Zhaoming (Frontiers in Cell and Developmental Biology, 2021)
Glucocorticoid-induced osteoporosis (GIOP) is the most common secondary osteoporosis and reduced bone formation was the main pathological change in GIOP. Our previous studies have shown that there was an imbalance between adipogenic and osteogenic differentiation in GIOP BM-MSCs and peroxisome proliferator-activated receptor γ2 (PPARγ2) played a vital role in this disorders. Here, we reported that there was an increase in ROS level and SENP3 expression in Dex-induced osteoporotic BM-MSCs, and enhanced adipogenesis and weakened osteogenesis in osteoporotic BM-MSCs might be caused by upregulated SENP3. Then we found that SENP3 de-SUMOylated PPARγ2 on K107 site to potentiate adipogenesis and weaken osteogenesis. These results may provide new strategy and target in the clinical diagnosis and treatment of GIOP.